2017
DOI: 10.1111/imre.12248
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Migration Policy Changes in Europe for Return Migration to Senegal

Abstract: This study questions the role of migration policy changes in France, Italy, and Spain for return migration to Senegal, by analyzing biographic data from the Migration between Africa and Europe (MAFESenegal) survey and the contextual data of the Determinants of International Migration (DEMIG) VISA and DEMIG POLICY databases that cover major changes in migration policies in these destination countries for the different categories of migrants. Event history logistic regressions reveal that Senegalese migrants are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…6 Assuming that these remigrations are returns, these findings may illustrate that unstable sociopolitical and economic situations, including contexts of violence, at origin are likely to discourage migrants’ remigration. 7 They are also consistent with recent studies that underlined restrictive migration policies’ role in remigration decisions, especially for sub-Saharan African migrants, who are all the less likely to return as the possibility of moving back to the destination country is uncertain (Flahaux 2017).…”
Section: Resultssupporting
confidence: 81%
“…6 Assuming that these remigrations are returns, these findings may illustrate that unstable sociopolitical and economic situations, including contexts of violence, at origin are likely to discourage migrants’ remigration. 7 They are also consistent with recent studies that underlined restrictive migration policies’ role in remigration decisions, especially for sub-Saharan African migrants, who are all the less likely to return as the possibility of moving back to the destination country is uncertain (Flahaux 2017).…”
Section: Resultssupporting
confidence: 81%
“…While naturalization tends to deter return intentions (Bettin, Cela, and Fokkema 2018), citizenship facilitates intra-EU onward migration, especially to the UK (Ahrens, Kelly, and van Liempt 2016; Mas Giralt 2017). On the other hand, migration restrictions seem to encourage long-term settlement, as immigrants are less likely to risk leaving the host country if returning would be difficult (Czaika and de Haas 2017; Flahaux 2017). In that case, naturalized immigrants may be more likely to temporarily return since they would be able to come back to France more easily.…”
Section: Previous Literature and Theoretical Backgroundmentioning
confidence: 99%
“…2). Previous research on the Mexican, Congolese, and Senegalese contexts has shown that tougher conditions of entry and stay tend to deter migrants' return (Flahaux 2015;Flahaux 2017;Massey et al 2002;Massey and Pren 2012). There are two possible explanations.…”
Section: Trends In Returnsmentioning
confidence: 95%